RISK FACTORS FOR HOSPITALIZATION FOR A MAJOR ACUTE CARDIOVASCULAR EVENT AFTER ACUTE KIDNEY INJURY WITH FULL RECOVERY: A SINGLE CENTER EXPERIENCE. (June 2022) - Mahmoud, Nouha Ben; Hamouda, Mouna; Maatoug, Jihene; Salem, Meriem Ben; Salah, Manel Ben; Letaief, Ahmed; Aloui, Sabra; Skhiri, Habib
Abstract : Objective: Acute kidney injury (AKI) was found to be associated with an increased risk of major adverse cardiovascular events (MACE) in the general population. We aim to evaluate the risk factors of patients having had an episode of AKI with full recovery exposing them to the risk of MACE Design and method: We conducted a retrospective single center study including all patients hospitalized in the nephrology ward since 2002 to 2015, which experienced an AKI episode with full recovery. AKI was defined according to KDIGO criteria. Our primary outcome was to identify risk factors in our population exposing them to MACE after AKI. Results: Our study included 107 men and 107 women with median age was 61 years. KDIGO stage 3 was the major stage (115 patients), 31 of whom required hemodialysis. Hypertension was found to be the major co morbidities in our population with 37.4% of patients followed by diabetes (32.2%). Median creatinine was 3.79 mg/l (1.26 – 34.57 mg/l). Most patients had anemia (65.4%). Among 176 patients for whom we have followed up, in the short, medium and long term: 19, 20 and 2 patients had respectively developed a MACE. The characteristics of patients according to the occurrence of MACE or not are illustrated by the table 1 The risk factors found in our population were presence of co morbidities, vascular disease and anemia in univariate analysis and only anemia in multivariate analysis (table 2). Patients with anemia and vascular disease had 2.4 times more the risk ti develop MACE after AKI with full recovery than patients without anemia and no past history of vascular disease Conclusions: Patients with anemia, past history of vascular disease are at risk of MACE after AKI with full recovery and those patients should be better monitored in the short, medium and long term. Our aim is to detect the MACE earlier so we decrease the cardiovascular mortality